Measuring Board of Director Performance: An Overview and Future Research Opportunities - Nowland, John (Universitas Airlangga, 2016)
This article provides a brief overview of the literature on board of director performance, highlighting the difficulties in attempting to directly measure the performance of boards of directors and how various studies have tackled this challenge. As an illustration, I show that two current measures of board of director performance, board meeting activity and director attendance, suggest that the boards of Asian firms do not compare favorably to the boards of firms from developed markets. Suggestions for future research on the performance of corporate boards are provided, as well as implications for board of director practices in Asia.